(untitled) (Al-Qamar, 2022)
In the realm of literary analysis, the application of structuralist principles help to shed light on the intricate layers of meaning woven into the fabric of short stories. For understanding and interpreting the text, structuralist analysis has been applied to five short stories selected from Paulo Coelho’s Stories for Parents, Children, and Grandchildren Volume 1. The aim of this study is to understand and examine real, true messages and to get the correct study in a particular way from the short stories. This study is conducted on flash fiction a type of short story. Structuralist analysis is concerned with the umbrella term Structuralism, and it has been defined in a very simple way. This is a non-emprical research methodology and textual analysis have been applied. Roland Barthes’ five codes, namely, the hermeneutic code, the proairetic code, the connotative code, the symbolic code, and the cultural code are applied, which help to discover the way to find out the meaning of the text.